(untitled) (Global Journal of Human-Social Science, 2016)
At the time of independence of the Republic of Uzbekistan and the Republic of Karakalpakstan there was done a great work in training young people for family life. It should be noted the development of teaching materials and the introduction of the subject «Psychology of Family Life» into the curriculum of vocational colleges and academic lyceums which is studied in the third year, when the question is actual in this age of students. For educational institutions in Karakalpakstan there was designed Karakalpak version of the tutorial, which is being studied by students for over 10 years. It is well known that one of the leading factors in the strength of the family and a healthy psychological environment it is personal and theoretical readiness of young people to create a family. There are a number of researches devoted to the study of young people’s ideas about family life and the criteria of their readiness for marriage. In order to strengthen the family as in a learning course "Psychology of Family Life", and in the life it is need effectively cultivating and use the family type of holiday: the resorts, sanatoriums, rest homes, as well as various tourist trips in the country and abroad.